2020
DOI: 10.22190/fupes191016052s
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Exercise Program on Coordination and Explosive Power in University Dance Students

Abstract: The aim of this research is to determine the effects of a ten-week modern and recreational dance exercise program and trunk and leg muscle strengthening exercises on the coordination and explosive power of student-age female dancers. The total number of participants was 54, of which 27 made up the experimental group who participated in an experimental exercise program and 27 the control group. The experimental group performed Hip Hop and Dancehall dances and trunk and leg muscle strengthening exercises 3 times… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 20 publications
1
9
0
2
Order By: Relevance
“…Previous studies that observed the effect of training programs in the jump height of dancers have also obtained improvements in this variable with values pre-post diverging between 16.9 (2.9) cm and 18.9 (2.7) cm ( p < 0.001, d = 0.36: small ES) pre-post 30 weeks of a plyometric training program and in CMJ with arm swing dancers jumped 21.5 (3) cm vs. 25 (2.8) cm ( p < 0.001, d = 1.21: large), an ES equal to our findings in CMJ ( Mlsnová and Luptáková, 2017 ); 22.50 (4.21) cm and 25.47 (4.95) cm pre-post a 10-week modern and recreational dance exercise program and trunk and leg muscle strengthening exercises ( Stošić et al, 2020 ); 26.93 (2.78) cm and 27.35 (3.06) cm pre-post an 8-week protocol ( Tsanaka et al, 2017 ); and 29.3 (3.2) cm and 33.5 (3.7) cm with a significant improvement ( Escobar-Alvarez et al, 2019 ) aligned with our findings. Still, in studies without interventions, CMJ height values ranged between 23.34 (1.72) cm in dancers aged 15 (1.07) years ( Rojano-Ortega, 2020 ) and 28.29 (3.42) cm in dancers aged 18.94 (1.32) years ( Alvarez et al, 2020 ).…”
Section: Discussionsupporting
confidence: 75%
See 3 more Smart Citations
“…Previous studies that observed the effect of training programs in the jump height of dancers have also obtained improvements in this variable with values pre-post diverging between 16.9 (2.9) cm and 18.9 (2.7) cm ( p < 0.001, d = 0.36: small ES) pre-post 30 weeks of a plyometric training program and in CMJ with arm swing dancers jumped 21.5 (3) cm vs. 25 (2.8) cm ( p < 0.001, d = 1.21: large), an ES equal to our findings in CMJ ( Mlsnová and Luptáková, 2017 ); 22.50 (4.21) cm and 25.47 (4.95) cm pre-post a 10-week modern and recreational dance exercise program and trunk and leg muscle strengthening exercises ( Stošić et al, 2020 ); 26.93 (2.78) cm and 27.35 (3.06) cm pre-post an 8-week protocol ( Tsanaka et al, 2017 ); and 29.3 (3.2) cm and 33.5 (3.7) cm with a significant improvement ( Escobar-Alvarez et al, 2019 ) aligned with our findings. Still, in studies without interventions, CMJ height values ranged between 23.34 (1.72) cm in dancers aged 15 (1.07) years ( Rojano-Ortega, 2020 ) and 28.29 (3.42) cm in dancers aged 18.94 (1.32) years ( Alvarez et al, 2020 ).…”
Section: Discussionsupporting
confidence: 75%
“…Other studies also showed significant improvements in the jumping performance of dancers (Wang et al, 2010;Komeroski et al, 2016;Tsanaka et al, 2017;Escobar-Alvarez et al, 2019;Stošić et al, 2020) and rhythmic gymnasts (Piazza et al, 2014;Dobrijević et al, 2018;Dallas et al, 2020) as a result of training interventions, and the improvements in jumping performance are consistent with previous findings in ballet dancers (Escobar-Alvarez et al, 2019;Alvarez et al, 2020) and in other sports disciplines (Jimenez-Reyes et al, 2016, Jiménez-Reyes et al, 2019. We suggest an exercise prescription based on the individual needs and the physical demands of ballet, jazz, and contemporary dancers as referred to in previous studies (Alvarez et al, 2020;Dowse et al, 2020).…”
Section: Almost Certainlymentioning
confidence: 88%
See 2 more Smart Citations
“…This may be promoted by aerobic gymnastics, because basic gymnastics has a positive effect on the children's muscular strength and endurance and the explosive power of the upper and lower limbs. Previous studies have shown that aerobic gymnastics has a positive effect on balance ability [29][30][31], body coordination [32][33][34][35], muscle strength, muscle endurance, and flexibility [30,36,37] of the practitioner. Strength, balance, and body coordination contribute to the development of participants' motor skills and physical fitness, which is essential for building a healthier life.…”
Section: Effects Of the Arg On Improving The Physical Fitnessmentioning
confidence: 99%